The Negotiation of Indonesian Cultural Identity in the Arabic Subtitles of the Film Habibi and Ainun - Alsadika Ziaul Haq; Zainal Arifin Ahmad; Abdul Munip; Adhi Setiyawan (JPI: Jurnal Pustaka Indonesia, 2025)
Audiovisual translation constitutes a critical site of intercultural mediation, particularly when films convey culture-specific meanings across linguistically and socially distinct audiences. This study investigates the negotiation of Indonesian cultural identity in the Arabic subtitle translation of Habibie & Ainun. Employing a qualitative descriptive design with comparative and interpretative analysis, the study examines Indonesian dialogue units containing culture-specific references and their corresponding Arabic subtitles. The data were collected through audiovisual observation, transcription, coding, and classification based on social, material, and religious cultural domains. The findings demonstrate that cultural identity negotiation is most pronounced in social-cultural expressions, including honorifics, kinship terms, colloquial expressions, idioms, and interpersonal politeness markers. These items were frequently rendered through pragmatic equivalence, cultural substitution, modulation, and domestication to preserve relational meaning and target-language naturalness. Material-cultural references, such as domestic objects, spatial expressions, and technological terms, were more often translated through literal or descriptive equivalence because their referents were relatively accessible within the Arabic cultural framework. Religious expressions showed the lowest degree of cultural resistance due to shared Islamic linguistic and theological roots, although contextual modulation remained necessary in emotionally charged utterances. The study concludes that Arabic subtitling of Habibie & Ainun functions not as a mechanical linguistic transfer but as a culturally situated process of meaning negotiation. The findings underscore the role of subtitle translators as intercultural mediators who balance Indonesian cultural visibility with Arabic audience comprehensibility.